An interprofessional urban health elective focused on the social determinants of health - Pinto, Andrew; To, Matthew; Rucchetto, Anne; Sharma, Malika; Rouleau, Katherine (Canadian Medical Education Journal, 2018)
Background: More than half of the world’s population now lives in cities. Health professionals should understand how social factors and processes in urban spaces determine individual and population health. We report on lessons from an interprofessional urban health elective developed to focus on the social determinants of health (SDOH). Methods: An interprofessional committee developed an urban health elective based in downtown Toronto. Course objectives included promoting collaboration to address SDOH, identifying barriers to care, accessing community-based resources, and learning to advocate at individual- and community-levels. Results: Seventeen students from eight disciplines participated during the 2011-2012 academic year. Sessions were co-facilitated with community partners and community members identified as experts based on their personal experience. Topics included housing, income and food security, Indigenous communities in urban spaces, and advocacy. Students collaborated on self-directed projects, which ranged from literature reviews to policy briefs for government. Students particularly valued learning about community agencies and hearing from people with lived experience. Conclusion: The specific health challenges faced in urban settings can benefit from an interprofessional approach informed by the experiences and needs of patient communities. This elective was innovative in engaging students in interprofessional learning on how health and social agencies collaborate to tackle social determinants in urban spaces.